Tomorrow ebook - Milligan, Peter (Tomorrow (2020)., 2020)
A shocking new story for 2020 by critically acclaimed and legendary writer Peter Milligan, breakout artist Jesús Hervas, and dynamic colorist James Devlin.When a Russian computer virus jumps the species barrier and wipes out most of the adult population, the world falls precariously into the hands of the next generation. In the wake of devastation, musical prodigy Oscar Fuentes is separated from his twin sister Cira. Without the support of each other and stranded on opposite sides of the country, they're soon swept into the rapidly-evolving networks of diverse teenage groups-turned-gangs. Can Oscar find his way back to Cira...or will they be lost to each other forever, in a dangerous makeshift civilization that is mercilessly replacing the past?Collects Tomorrow #1-#5. Author: Peter Milligan. Illustrator: Jesus Hervas, James Devlin, Clem Robins.